Piscirickettsia salmonis pathogenicity: using the damage-response framework to look beyond smoke and mirrors - Felipe C. Cabello; Ana Millanao; Henry P. Godfrey (mBio)
ABSTRACT Piscirickettsia salmonis is a globally distributed aquatic bacterium and a component of the normal salmon microbiome. It has significant biological and economic impact on Chilean salmon aquaculture due to the highly fatal disease, piscirickettsiosis. Unsuccessful attempts to prevent and treat this disease have resulted in heavy use of antimicrobials with adverse effects on the aquatic environment and piscine and human health. Evidence suggests P. salmonis could be a bacterium with relative pathogenic potential on farmed salmonids and other fishes that triggers piscirickettsiosis under particular conditions in the salmon and its environment. Application of a damage-response framework analysis could define the steps from asymptomatic P. salmonis infection to symptomatic disease, help tailor improved approaches to disease prevention and management, and, in turn, help avoid heavy use of antimicrobials which have global effects on animal health, human health, and environmental biodiversity (the One Health concept).